PERAN PEMBELAJARAN KEWIRAUSAHAAN DAN DUKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA PRODI PENDIDIKAN BISNIS UNIVERSITAS NEGERI SURABAYA - Errangga Pratama; Renny Dwijayanti (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
This study aims to analyze the influence of entrepreneurship learning and family support on student’s entrepreneurial interest in the Business Education Study Program at Surabaya State University. The research is motivated by the importance of educational experiences and family environments in shaping entrepreneurial interest in students. This study used a descriptive quantitative approach with a sample of 209 students determined using slovin formula. Data collection was conducted using a questionnaire, then analyzed through validity and reliability test, classical assumption tests, multiple linier regression, T-test, and F-test. The results indicate that entrepreneurship learning and family support have a positive and significant effect on entrepreneurial interest, both partially and simultaneously. Together, these two variables contribute 44,2% to student’s entrepreneurial interest, while the remaining 55,8% is influenced by other factors outside the study. These findings confirm that a positive learning experience and strong family support play a crucial role in fostering student’s entrepreneurial interest.